THE EFFECT OF TEAMWORK AND WORK DISCIPLINE IN IMPROVING TEACHER PRODUCTIVITY - Bakri Hasanuddin; Harnida Wahyuni Adda; Faruq Lamusa; Moh Fadigal (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the role of teamwork synergy and work discipline as an important foundation in increasing teacher productivity at SMP Negeri 18 Palu. The method used is quantitative with a population and sample of 30 people including the principal and teachers. The sampling technique is a saturated sampling approach. Data collection in this study was obtained through interviews and questionnaire distribution which were then processed using the SPSS ver. 25 application. The data analysis technique used is multiple linear regression analysis. The results obtained state that: (1) partially teamwork has a positive and significant effect on increasing teacher productivity; (2) partially work discipline has a positive and significant effect on increasing teacher productivity; and (3) simultaneously there is a significant influence between teamwork and work discipline on teacher productivity